2022
DOI: 10.3389/fbioe.2022.825231
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Repair Effects of the NCF-Col-NHA Aerogel Scaffold Loaded With SOST Monoclonal Antibody and SDF-1 in Steroid-Induced Osteonecrosis

Abstract: In the current study, we synthesized nanocellulose (NCF)-collagen (Col)-nano hydroxyapatite (NHA) organic-inorganic hybrid aerogels loaded with stromal cell derived factor-1 (SDF-1) and sclerostin monoclonal antibody (SOST McAb) and investigated their ability to repair steroid-induced osteonecrosis. Rabbit bone marrow mesenchymal stem cells (BMSCs) and human vascular endothelial cells (HUVECs) were used for the in vitro study. A rabbit steroid-induced osteonecrosis model was used for the in vivo study. The bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Bone marrow mesenchymal stem cells (BMSCs) and HUVECs can attach to surfaces, group together, and carry out their various bioactive functions, according to in vitro research. Live/dead cell staining results further substantiate the superior biocompatibility of the collagen-HA scaffold, favoring cell development and fostering osteogenesis and vascularization [72,73]. Therefore, scaffolds formed by hydroxyapatite and collagen together have promising applications in artificial bone graft substitutes and tissue engineering scaffolds [74].…”
Section: Natural Polymers (Table 2) Collagenmentioning
confidence: 80%
“…Bone marrow mesenchymal stem cells (BMSCs) and HUVECs can attach to surfaces, group together, and carry out their various bioactive functions, according to in vitro research. Live/dead cell staining results further substantiate the superior biocompatibility of the collagen-HA scaffold, favoring cell development and fostering osteogenesis and vascularization [72,73]. Therefore, scaffolds formed by hydroxyapatite and collagen together have promising applications in artificial bone graft substitutes and tissue engineering scaffolds [74].…”
Section: Natural Polymers (Table 2) Collagenmentioning
confidence: 80%
“…As an example toward future clinical translation, large bone defect is common that may be caused by incidence, bone fracture, and tumor. [4,[18][19][20] It is difficult for a single 3D-bioprinted replacement tissue to completely repair large and oftentimes irregular bone defect. Therefore, our modular assembly method provides a potential treatment option.…”
Section: Resultsmentioning
confidence: 99%
“…By controlling the ratio of collagen to carboxymethyl cellulose in the template, the osteoinductivity, the osteoconductive, and the mechanical strength of composites could be changed and adjusted according to the requirement of BTE [ 127 ]. Xu et al prepared nanocellulose–collagen (COL)-nanohydroxyapatite(n-HA) organic–inorganic hybrid aerogels by adding collagen and HA into cellulose aerogels and found that the composite aerogels exhibited a porous 3D structure with high compressive strength, excellent osteogenesis, and angiogenesis abilities both in vitro and in vivo [ 119 ]. Based on the above-mentioned research, it is safely concluded that the organic–inorganic hybrid materials based on the combination of Col and nanocellulose could construct multilevel bionic scaffolds from macro to micro and present great potential for repairing bone defects.…”
Section: Application Of Nanocellulose-based Aerogels In Btementioning
confidence: 99%
“…The potential growth factors which could be control released by the nanocellulose aerogels for BTE include bone morphogenetic protein (BMP), vascular endothelial growth factor (VEGF), stromal cell-derived factor-1 (SDF-1), sclerostin monoclonal antibody, etc. [ 119 ]. Among them, BMP and VEGF are commonly utilized factors to promote osteogenesis and angiogenesis.…”
Section: Nanocellulose Aerogels-based Controlled Releasing System For...mentioning
confidence: 99%